A high pressure chamber development for the investigation of spray characteristics - A. K. Amirruddin; M.H. Razali; Firmansyah; Nicolas, P.; A.A. Abdul Rashid (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.